Life-span development - Santrock, John W (New York, NY, 2024)
As a master teacher, John Santrock connects current research with real-world application, helping students see how developmental psychology plays a role in their own lives and future careers. Through an integrated learning goals system, this comprehensive and chronological approach to lifespan development helps students gain the insight they need to study smarter, stay focused, and improve performance.